The Degree of Possessing E-Learning Skills by Secondary Stage Teachers from School Principals’ Perspectives in Amman Governorate - Al-Ashush, Hasnah AbdelHafeez (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the degree of possessing e-learning skills to which chemistry teachers in the secondary stage from the point of view of school directors in the capital of Jordan Amman ; that study followed up the descriptive survey approach , the whole study consisted of (104) directors male and female for the first semester 2021/2022 which (35) were males and (69) females, and this is related to the variables (the gender of the teacher, the educational qualification, the number of years of experience, the work sector). To achieve this goal, a scale of e-learning skills consisting of (37)items was developed and it has been identified from credibility and solidarity of the scale and it has been applied on a sample consisted of (104) directors of public and private schools in the Capital city Amman, and the results showed that the degree of possession of chemistry teachers in the secondary stage of e-learning skills from the point of view of school directors in the Capital Amman, was medium, and the degree of possession of skills (electronic education management, techniques) E-learning, electronic research) is medium, while the degree of possession of (electronic assessment) skills is low, and the results also showed up that there were no statistically significant differences between the arithmetic averages of the degree of possession of teachers in the secondary stage of e-learning skills from the point of view of school directors in the Capital Amman, due to the variables (teacher gender, educational qualification, number of years of experience), and the presence of a statistically significant difference for the sector variable in favor of private schools. In light of the results, the study recommended recommendations, the most important of which are: Strengthening the infrastructure of public schools, providing them with hardware and computer programs, rehabilitating teachers and training them to raise their skills in dealing with e-learning, and conducting more studies on other variables and different areas.
Keywords: chemistry teachers; e-learning skills; school principals